Total arterial revascularization in patients with multi–vessel coronary artery disease: modern insight on conduit selection - Stukov, Y. Y.; Rudenko, S. A.; Rudenko, A. V.; Lazoryshynetz, V. V. (Ukrainian Journal of Cardiovascular Surgery, 2018)
Coronary artery bypass grafting (CABG) remains the most common operation performed by cardiac surgeons today. Fundamental basis of CABG is to reestablish perfusion to the myocardium, however there are different approaches in accomplishing this goal. The collection of scientific publications suggest the use of multiple arterial conduits in patients of young age, preferable without advanced comorbidity and low body surface area. Despite common use of saphenous vein grafts, lots publications demonstrate advantages of arterial conduits. Internal mammary artery (IMA) has patency rates in the region of 90–95% ten to fifteen years after CABG. Based on superior long-term results of the internal mammary artery (IMA), other arteries is being used in CABG. Radial artery (RA) nowadays it is the most popular arterial graft after the IMA in both low- and high-risk patients. Although, this conduit is underused, despite numerous observational studies, which documented excellent RA patency of 89% at 10 years. Furthermore RA and ITA grafting shows a strong protective effect against native coronary artery disease progression in symptomatic patients after CABG. The constellation of recent data and 2018 guidelines of European Society of Cardiology and European Association for Cardiothoracic Surgeons on myocardial revascularization suggest performing total arterial revascularization in patients with multi-vessel coronary artery disease. Purpose. Literature review on recent data in surgical revascularization using multiple arterial grafts in patients with multi-vessel coronary artery disease. Conclusions. Total arterial revascularization is safe and effective method in treatment of multi-vessel coronary artery disease. There is undoubted benefit of total arterial revascularization in short-, mid- and long–term results in frames of angina recurrence, major adverse cardiac events and redo surgery, associated with graft failure, compared to saphenous vein grafts. Total arterial revascularization may have protective effect on native coronary artery from disease progression, along with excellent patency rates in patients after CABG. However, clinical choice of grafts should be based on patient’s general condition, coronary artery anatomy and severity of stenosis.